2019
DOI: 10.1186/s13287-019-1458-8
|View full text |Cite
|
Sign up to set email alerts
|

lncRNAs: function and mechanism in cartilage development, degeneration, and regeneration

Abstract: With the increasing incidence of cartilage-related diseases such as osteoarthritis (OA) and intervertebral disc degeneration (IDD), heavier financial and social burdens need to be faced. Unfortunately, there is no satisfactory clinical method to target the pathophysiology of cartilage-related diseases. Many gene expressions, signaling pathways, and biomechanical dysregulations were involved in cartilage development, degeneration, and regeneration. However, the underlying mechanism was not clearly understood. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 145 publications
0
43
0
Order By: Relevance
“…Therefore, understanding the potential pathogenesis of meniscus degeneration is of considerable significance to identify the therapeutic targets and is beneficial to study the disease further and to search for the biotherapies of the disease. Accumulating studies highlighted the role of lncRNAs in disease pathology from the view of gene expression regulation [ 21 , 30 , 31 ]. To illuminate the mechanism of meniscus degeneration of KOA, we used differential expression analysis, WGCNA, and ceRNA networks to identify biomarkers in samples of the meniscus from KOA and non-KOA subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the potential pathogenesis of meniscus degeneration is of considerable significance to identify the therapeutic targets and is beneficial to study the disease further and to search for the biotherapies of the disease. Accumulating studies highlighted the role of lncRNAs in disease pathology from the view of gene expression regulation [ 21 , 30 , 31 ]. To illuminate the mechanism of meniscus degeneration of KOA, we used differential expression analysis, WGCNA, and ceRNA networks to identify biomarkers in samples of the meniscus from KOA and non-KOA subjects.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are involved in multiple pathological processes and biological functions such as malignancy, differentiation, apoptosis, development, survival, and proliferation [31]. LncRNAs can impact biological pathways and cellular activities by different mechanisms; for example, they can target transcription factors, block transcription of nearby genes, direct methylation complexes, and initiate chromatin remodelling [32,33] ( Figure 2B). During the progression of liver fibrosis, a number of lncRNAs play roles in the promotion or suppression of fibrosis through binding of ceRNAs to miRNAs and directly binding proteins [34][35][36].…”
Section: Function and Mechanism Of Lncrnasmentioning
confidence: 99%
“…Many current studies have showed that lncRNAs regulate gene expression indirectly via transcriptional regulation, posttranscriptional modification, and modulation of microRNA (miRNA) activities [21,27,28] . Among them, the most common mechanism is that lncRNAs can function as competing endogenous RNAs (ceRNAs) to protect mRNAs by competing for their targeting microRNAs [19,20] .…”
Section: Suppression Of Gm12664 Expression Decreased Ffa-induced Trigmentioning
confidence: 99%